Examination of orthopedic & athletic injuries - Starkey, Chad, 1959-; Brown, Sara D. (Philadelphia : F.A. Davis Company, 2015)
"Perform accurate evaluations of orthopedic injuries. In this book, organized by body region, each chapter begins with a review of anatomy and joint function; proceeds through clinical examination, specific pathologies, and related selective tissue tests (specific tests); and concludes with a discussion of intervention strategies and on-field or initial management of specific conditions"--Back cover
Examination process -- Examination and management of acute conditions -- Evidence-based practice in the diagnostic process -- Injury pathology nomenclature -- Musculoskeletal diagnostic techniques -- Assessment of posture -- Evaluation of gait -- Foot and toe pathologies -- Ankle and leg pathologies -- Knee pathologies -- Patellofemoral pathologies -- Pelvis and thigh pathologies -- Lumbosacral pathologies -- Cervical and thoracic spine and thorax pathologies -- Shoulder and upper arm pathologies -- Elbow and forearm pathologies -- Wrist, hand, and finger pathologies -- Eye pathologies -- Face and related structure pathologies -- Head and acute cervical spine pathologies
Includes bibliographical references and index
1 13
Keywords: Orthopedics -- Diagnosis; Sports injuries -- Diagnosis